Cancer du sein, troubles émotionnels et coping religieux - Kouami ADANSIKOU; Kossi Blewussi KOUNOU; Zinsou Selom DEGBOE; Nénon TOSSOU (Revue Hybrides)
Cancer is a feared disease because it is potentially painful and fatal. The representation of chronic illness influences the strategies put in place by individuals who suffer from it. They develop reactions to control, reduce or simply tolerate the aversive situation. The present study aims to establish a link between the representation of breast cancer and religious coping strategies through emotional disorders in women with breast cancer. A parallel convergent mixed method was adopted using a questionnaire and a semi-structured interview on a sample of 78 patients. Statistical processing of the data was carried out with the Sphinx Lexica Plus software. The results show on one hand that the emotional disorders observed in women with breast cancer are linked to their representation of the disease and on the other, the religious coping strategies adopted depend on the emotional disorders. Emotions are reignited by deadly diseases like breast cancer. Faced with this existential anxiety, religion appears to be an important therapeutic lever for giving meaning to the illness and adapting to it.